Social Welfare and Religion: A Social Action of Al-Karomah Mosque in the Pandemic Era - Tasrif, Khoirun Nisa'; Setiyani, Wiwik (The Sunan Ampel Review of Political and Social Sciences, 2021)
The Covid-19 pandemic has colored socio-religious life to this day. One way to respond to the pandemic is by carrying out social activities that benefit the community. This article will discuss three academic problems, including; First, how did the idea of sadaqah centelan come about during the Covid-19 pandemic. Second, how to innovate social action with sadaqah centelan. Third, how the community responds to sadaqah centelan as social action innovation. This research was conducted at the Al-Karomah mosque in Wiyung Surabaya. The data collection method used in-depth interviews with people directly involved in the sadaqah centelan activity at the Al-Karomah mosque. Some of the research findings include; first, effectiveness, efficiency, and on target with the assistance provided by the mosque for worshipers who stop at the mosque or live around the Wiyung area; second, the implementation of the sadaqah centelan is carried out by taking the alms that the mosque management has provided for congregations who have economic limitations. On the other hand, those who can give alms can take the alms package program, which varies nominal value. Third, the community appreciates the initiation of the committee, which can provide convenience and comfort to the congregation. Sadaqah centelan is an effective and efficient strategy in reducing the risk of spreading covid-19. The innovation in charity teaches Muslims to increase social worship and create a social distraction during the pandemic can be an inspiration for other mosques in grounding alms in innovative ways.